Joint patrols at the EU's southern border: Security and development in the control of African migration - Roderick Parkes (Stiftung Wissenschaft und Politik (SWP), 2006)
In August 2006, the EU launched the first of two projected joint border patrols at its southern border in response to mass inflows of irregular migration from Africa. This development has simultaneously been criticised as a further buttress of 'fortress Europe' and defended as performing an important humanitarian task. It cannot, however, be judged in isolation, and must be set within the context of the full range of migration-control measures that are directed at Africa. This broader picture indicates that if the EU is serious in its aim of effectively controlling migration from that continent without compromising the rights of migrants and the interests of third countries, it will have to adopt an approach that makes use of the full range of policy tools available to it and takes a longer-term, curative perspective. (SWP Comment / SWP)
Keywords: 320